2019
DOI: 10.32952/atauniiletisim.552336
|View full text |Cite
|
Sign up to set email alerts
|

Yeşi̇l Ürün İleti̇şi̇mi̇ Kapsaminda Tüketi̇ci̇leri̇n Yeşi̇l Ürünlere Yöneli̇k Algi Ve Bi̇lgi̇ Düzeyleri̇

Abstract: Simge AKSU * ÖZET 1960'lardan bu yana artan çevre kirliliği ve yaşanan çevre felaketleri tüketicileri çevre konusunda daha hassas bir hale getirmiştir. Tüketimin sürekli teşvik edildiği günümüzde çevreye duyarlı tüketiciler, tüketim pratiklerinde çevreyi göz önünde bulundurarak tüketimde bulunmaktadırlar. Bu araştırmanın temel amacı tüketicilerin yeşil ürünlere yönelik görüşlerini ve bilgi düzeylerini keşfetmektir. Tüketici tutumları üzerine gerçekleştirilen pek çok araştırma tüketicilerin çevreci ürünlere yön… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Individuals tend to develop sustainable consumption intentions because they believe that undertaking such behaviour will be regarded as desirable by their significant others. Although these results are consistent with many previous studies (Armitage & Conner, 2001; Emekçi, 2018; Onel & Mukherjee, 2017; Thøgersen & Ölander, 2002; Vermeir & Verbeke, 2008) but contradicts with the findings of (Korkmaz & Sertoğlu, 2013). Research by Paul et al, (2016) also highlighted that subjective norm is the weakest predictor of sustainable purchasing intentions.…”
Section: Discussionsupporting
confidence: 74%
“…Individuals tend to develop sustainable consumption intentions because they believe that undertaking such behaviour will be regarded as desirable by their significant others. Although these results are consistent with many previous studies (Armitage & Conner, 2001; Emekçi, 2018; Onel & Mukherjee, 2017; Thøgersen & Ölander, 2002; Vermeir & Verbeke, 2008) but contradicts with the findings of (Korkmaz & Sertoğlu, 2013). Research by Paul et al, (2016) also highlighted that subjective norm is the weakest predictor of sustainable purchasing intentions.…”
Section: Discussionsupporting
confidence: 74%
“…It has been concluded that subjective norms for sustainable consumption behavior have a significant effect on sustainable consumption intention. Some of the previous studies emphasize that the intention for environmentally conscious consumption is driven by subjective norms (Armitage & Conner, 2001; Beck & Ajzen, 1991; Conner & Armitage, 1998; Emekçi, 2017; Hopper & Nielsen, 1991; Onel & Mukherjee, 2017; Stern & Dietz, 1994; Thøgersen & Ölander, 2002). Vermeir and Verbeke (2008) stated that subjective norms have an additional positive effect on purchase intention.…”
Section: Discussionmentioning
confidence: 99%
“…In the first part, there are six items aiming to reach demographic information of consumers. These are the variables of age, marital status, gender, educational status, household income, and the number of people in the household that were frequently encountered in previous studies that were studied to determine the sustainable consumption intention in the literature (de Leeuw et al, 2015; Emekçi, 2017; Korkmaz & Sertoğlu, 2015; Roberts, 1996). In the second part of the questionnaire, 36 items adapted from the scales used in previous studies in the literature to determine the final sustainable consumption behavior of consumers were included in the study (Dean et al, 2012; Fishbein & Ajzen, 2010; Onel, 2014; Paul et al, 2016; Roberts, 1996; Smith et al, 1994; Stern et al, 1999; Tanner & Kast, 2003; Thøgersen, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%